EXTENSÃO DA VIDA DE PRATELEIRA DE OVOS PARA CONSUMO PELA COBERTURA COM BORRA DE PRÓPOLIS - BAIRROS, Eliane Corrêa; GARCIA, Elis Regina de Moraes; ANDRADE, Gislaine da Cunha de; SANTANA, Patrícia Gomes; SOUSA, Gabrieli Costa de; SILVA, Camila de Souza (ANAIS DO ENIC, 2018)
-